2005
DOI: 10.1093/aob/mci195
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Aquaporin Subtypes (PIP1, PIP2 and γ-TIP) is Tissue Dependent in Soybean (Glycine max) Root Nodules

Abstract: PIPs and gamma-TIP aquaporins are highly expressed in both plasmalemma and tonoplast of nodule IC-cells. This distribution is consistent with the putative role of water fluxes associated with the regulation of nodule conductance to O2 diffusion and the subsequent ATP-dependent nitrogenase activity. In the endodermis, these aquaporins might also be involved in nutrient transport between the infected zone and vascular traces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…O 2 concentration decreases sharply through the inner cortex, and the O 2 permeability is flexibly controlled by this layer (Witty andMinchin 1990, Hunt andLayzell 1993). It is hypothesized that a reversible exchange of intercellular water by the inner cortical cells plays a role in the regulation of nodule conductance to O 2 diffusion (Serraj et al, 1995, Fleurat-Lessard et al, 2005. There are lenticels outside of nodules and one layer of epidermis.…”
Section: Nodule Structure and Function Of Soybeanmentioning
confidence: 99%
“…O 2 concentration decreases sharply through the inner cortex, and the O 2 permeability is flexibly controlled by this layer (Witty andMinchin 1990, Hunt andLayzell 1993). It is hypothesized that a reversible exchange of intercellular water by the inner cortical cells plays a role in the regulation of nodule conductance to O 2 diffusion (Serraj et al, 1995, Fleurat-Lessard et al, 2005. There are lenticels outside of nodules and one layer of epidermis.…”
Section: Nodule Structure and Function Of Soybeanmentioning
confidence: 99%
“…These data suggest a role of this AQP in the physiology of symbiosis, although the precise role of Nod26 in ammonia permeation has yet to be demonstrated. PIP and TIP proteins are abundant in both the PM and tonoplast of the inner cortical cells (IC-cells) of Glycine max root nodules (Fleurat-Lessard et al 2005). This distribution is consistent with their putative role of water flux facilitation associated with the regulation of nodule conductance to O 2 diffusion and the subsequent ATP-dependent nitrogenase activity.…”
Section: A Role For Pips In Programmed Cell Death and Plant Microbe Imentioning
confidence: 99%
“…In fact, 5 plant aquaporin families have been structurally and functionally well-studied and characterized [26,27]. A recent study showed a significant similarity between the amino acid sequences of soy, spinach, corn, tomato, and tobacco with human aquaporin epitope 207-232 [28].…”
Section: Introductionmentioning
confidence: 99%